Inserção da energia eólica na matriz energética do Ceará - Melo, Francisca Dayane Carneiro (2010)
That alternative energy is assuming an increasing role in cenary due to strong global because the environmental heat that these offer. In Brazil, specifically in Ceará, This reality is growing. The state operative has a capacity generates installed capacity of 1066.034 MW, distribute Of plants and in 15 wind farms for a total of 448.134 MW, 1 Central Small Hydropower Trica - PCH (4 , 0 MW) and 11 Thermoelectric Power Plants - UTE (613, 9 MW MW). This set, The Ceará has taken the lead the national capacity to generate the energy eletrical from the winds which operates the future the more power and 2 beverages provided by the Program of Incentives to Alternative Sources - PROINFA increase considerably involved the source and in your energetic matrix policy. The ability to generate And wind power be installed 5times higher than in 2009, with an increasing 1598 GWh / year in 2010 through "s of installs Of the 27 projects granted by Ag Engineering Nacional electric Energy - ANEEL. Of these, 25 s To generate The clean and refreshing , tapping the potential and solar metallic state, and responsible for 99.5% of the pot o clock action, against the current 84.93% developments in opera the type UTE. In this way, and with the inclusion The new projects generate The clean energy el Electric, the state of Ceará power pass in pr coming years, a conditions the eletric energy demand for the conditions the self-sufficient o clock. The first auction The sole energy source and to wind power fosters inclusion Of new developments in Ceará. The Government response to the growing needs of industry and Metallic recently created a C Mara Sector wind power - CSE wind power as a way to contribute In the consolidation The production chain of this sector. However read considering that the new order of environmental zoning currently being discussed the power public no scope state power change the profile passive areas of exploits the potential and metallic and an evaluation the limit as this the inclusion the source of the energetic matrix State policy is necessary.